[PP.10.04] BLOOD PRESSURE RESPONSE TO RENAL DENERVATION ACCORDING TO THE PRESENCE OR ABSENCE OF RENAL ACCESSORY ARTERIES. (September 2016) - Jacobs, L.; Persu, A.; Hammer, F.; Renkin, J.; Widimsky, J.; Rosa, J.; Kjeldsen, S.E.; Elmula, F.E. Fadl; Elvan, A.; Czarnecka, D.; Olszanecka, A.; Gordin, D.; et al.
Abstract : Objective: Renal denervation (RDN) has been shown to be a feasible treatment in resistant hypertensive patients. Renal accessory arteries (RAs) are frequent (20–27%) but seldom accessible to RDN. As such, they may constitute an unaddressed source of sympathetic overactivity. The aim of this study was to investigate if the presence of accessory RAs influences blood pressure response to RDN in patients with resistant hypertension. Design and method: Patients were recruited from 6 expert centres, within the European Network Coordinating research on Renal Denervation (ENCOReD). All patients underwent 24-h BP measurements at baseline and 6 months after RDN. Patients were classified in type A (main RA > = 20 mm length and > = 4 mm diameter) or type B (main RA < 20 mm length or < 4 mm diameter) according to renal anatomy (Okada classification). Subtypes include A1 (no accessory RAs), A2 (with accessory RAs < 3 mm diameter), A3 (with accessory RAs > = 3 mm diameter), B1 (main RA < 20 mm in length) and B2 (RA < 4 mm diameter). Results: 114 resistant hypertensive patients (age 58.1 ± 11.2, 46% women) were included in the analysis. Seventy-six (66%) patients did not have accessory RAs (type A1) and 39 (34%) patients did have accessory RAs (on one or both sides). 24-hour ambulatory systolic/diastolic BP after RDN dropped by -6.4/-4.0 mmHg in patients with no accessory RAs (p < 0.006), compared to a non-significant + 0.2/-0.7 mmHg (p > 0.70) in patients with accessory RAs. (p > 0.08 for the baseline adjusted between-group difference). When adjusted for sex, age, body mass index, baseline 24-h systolic ambulatory blood pressure as fixed effects, and for centre as random effect, the difference in decrease in 24-h systolic ambulatory blood pressure between the 2 groups was -3.8 mmHg (95% CI: -10.7 to 3.1, p = 0.27). Conclusions: A significant blood pressure decrease after RDN was observed only in patients without RAs. However, the difference between blood pressure changes in patients with or without RAs did not reach statistical significance. Ongoing analyses will include more subjects, as well as information on performance of RDN in accessory RAs and the number of ablations on each side.